2010
DOI: 10.1021/ja106543j
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Biocompatible Nanoparticles for in Vivo Imaging Applications

Abstract: Iron−platinum alloy nanoparticles (FePt NPs) are extremely promising candidates for the next generation of contrast agents for magnetic resonance (MR) diagnostic imaging and MR-guided interventions, including hyperthermic ablation of solid cancers. FePt has high Curie temperature, saturation magnetic moment, magneto-crystalline anisotropy, and chemical stability. We describe the synthesis and characterization of a family of biocompatible FePt NPs suitable for biomedical applications, showing and discussing tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 63 publications
2
94
0
2
Order By: Relevance
“…35,[38][39][40][41] Furthermore, in the area of medical imaging, FePt NPs are considered to have great potential in MRI and MRI/CT dual-model imaging as a regenerative medicine. 31,33 However, we confirm that there is still a paucity of research on FePt NPs in the radiotherapy field, in which the NPs may hold potential. The current study reports the synthesis of 3.11±0.53 nm monodispersed FePt NPs by a chemical reduction method, and the coating of these NPs …”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…35,[38][39][40][41] Furthermore, in the area of medical imaging, FePt NPs are considered to have great potential in MRI and MRI/CT dual-model imaging as a regenerative medicine. 31,33 However, we confirm that there is still a paucity of research on FePt NPs in the radiotherapy field, in which the NPs may hold potential. The current study reports the synthesis of 3.11±0.53 nm monodispersed FePt NPs by a chemical reduction method, and the coating of these NPs …”
Section: Discussionmentioning
confidence: 52%
“…[27][28][29] Furthermore, compared to several commercial MRI/CT contrast agents, the superparamagnetic properties and X-ray absorption abilities of FePt NPs make them potential in vitro and in vivo dual-modality contrast agents (after surface engineering with functional molecules). [30][31][32][33] Based on the extremely high X-ray mass absorption coefficient of Pt, the hypothesis of the current study was that the NPs may increase the absorbed external beam dose in tumors, with decreased absorption of radiation in normal tissue and organs. Therefore, FePt NPs could be the precursor for CT, MRI, chemotherapy and radiotherapy all within one single agent, acting as a kind of multifunctional nanomedicine.…”
Section: Introductionmentioning
confidence: 99%
“…There are some special kind of nanostructured materials like bio-magnetic nanoparticles which is important to consider the physico-chemical and electro-magnetic properties of nanostructured materials specially MNPs which will be composed at least magnetic element. So, these materials has attracted much interest which has been caused to extend wide range of applications like ferro fluid solutions, magnetic storage devices, bio-sensing application, magnetic power generations and conversion, magnetic controlled drug delivery, magnetic resonance imagining as a contrast agents [61][62][63][64][65][66][67][68][69][70][71][72][73][74]. For biomedical applications, magnetic nanoparticles must (1) have a good thermal stability; (2) larger magnetic moment; (3) be biocompatible; (4) be able to form stable dispersion so the particles could be transported in living system; and (5) well response to AC magnetic fields.…”
Section: Biomedical Applications Of Fe 3 O 4 Magnetic Nanoparticlesmentioning
confidence: 99%
“…[16][17][18] The magnetization of FePt NPs up to ∼1000 emu cc −1 is higher than that of commonly used iron oxide (approximately 300-400 emu cc −1 ) and comparable to that of Co (∼1400 emu cc −1 ) and Fe (∼1700 emu cc −1 ), making them valuable candidates for magnetic resonance imaging. [19][20][21][22] It has been reported that FePt NPs display stronger contrast enhancement when compared with several commercial magnetic resonance imaging contrast agents (Feridex, MION, and Sinerem; AMAG Pharmaceuticals Inc., Lexington, MA, MGH Center of Molecular Imaging Research, Boston, MA, and Guerbet Group, Villepinte, France, respectively) according to their apparent transverse relaxivity values. 19,20 Therefore, FePt NPs can serve as dual modality contrast agents for molecular CT (computed tomography molecular imaging or MRI (magnetic resonance imaging) in vitro and in vivo after engineering their surfaces with functional molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] It has been reported that FePt NPs display stronger contrast enhancement when compared with several commercial magnetic resonance imaging contrast agents (Feridex, MION, and Sinerem; AMAG Pharmaceuticals Inc., Lexington, MA, MGH Center of Molecular Imaging Research, Boston, MA, and Guerbet Group, Villepinte, France, respectively) according to their apparent transverse relaxivity values. 19,20 Therefore, FePt NPs can serve as dual modality contrast agents for molecular CT (computed tomography molecular imaging or MRI (magnetic resonance imaging) in vitro and in vivo after engineering their surfaces with functional molecules. 21 Of particular interest, superparamagnetic FePt NPs have been derived from the anticancer activity of FePt NPs.…”
Section: Introductionmentioning
confidence: 99%